Paraquat Intoxication in Subjects Who Attempt Suicide: Why They Chose Paraquat - Seok, Su-Jin; Gil, Hyo-Wook; Jeong, Du-Shin; Yang, Jong-Oh; Lee, Eun-Young; Hong, Sae-Yong (The Korean journal of internal medicine, 2009)
Paraquat (PQ) has been used in suicide attempts; an estimated 2,000 toxic ingestions occur annually, with 60-70% mortality. We sought to determine why PQ is such a common agent for suicide attempts in Korea. We analyzed 250 cases (143 males, 107 females) of attempted suicide by PQ ingestion from January to December 2007. The procurement of the PQ was divided into two categories: purchased and preexisting. Men were more likely to have purchased PQ than women (66% vs. 22%, p=0.042). Additionally, men were more likely to be unmarried (n=34, 23.9% vs. n=10, 9.3%) or divorced or separated (n=16, 11.3% vs. n=5, 4.6%) than the women (p<0.001). The group who intentionally selected PQ (38.4%) consisted of 96 cases (54 males, 42 females) and the group who did not intentionally select PQ (61.6%) included 154 cases (89 males, 65 females). The incidence of PQ purchase was higher in the intentional selection PQ group (46.9% vs. 18.2%, p<0.01). Only 38% of patients who attempted suicide with PQ intentionally selected PQ. Thus, greater control of PQ availability is needed, especially in patients at risk.